Functional spheroid organization of human salivary gland cells cultured on hydrogel-micropatterned nanofibrous microwells. (November 2016) - Shin, Hyun-Soo; Kook, Yun-Min; Hong, Hye Jin; Kim, Young-Mo; Koh, Won-Gun; Lim, Jae-Yol
Graphical abstract: Abstract: Development of a tissue-engineered, salivary bio-gland will benefit patients suffering from xerostomia due to loss of fluid-secreting acinar cells. This study was conducted to develop a bioengineering system to induce self-assembly of human parotid epithelial cells (hPECs) cultured on poly ethylene glycol (PEG) hydrogel-micropatterned polycaprolactone (PCL) nanofibrous microwells. Microwells were fabricated by photopatterning of PEG hydrogel in the presence of an electrospun PCL nanofibrous scaffold. hPECs were plated on plastic dishes, Matrigel, PCL nanofibers, or PCL nanofibrous microwells. When the cells were plated onto plastic, they did not form spheres, but aggregated to form 3D acinar-like spheroids when cultured on Matrigel, PCL, and PCL microwells, with the greatest aggregating potency being observed on the PCL microwells. The 3D-assembled spheroids in the PCL microwells expressed higher levels of salivary epithelial markers (α-amylase and AQP5), tight junction proteins (ZO-1 and occludin), adherence protein (E-cadherin), and cytoskeletal protein (F-actin) than those on the Matrigel and PCL. Furthermore, the 3D-assembled spheroids in the PCL microwells showed higher levels of α-amylase secretion and intracellular calcium concentration ([Ca 2+ ] i ) than those on the Matrigel and PCL nanofibers, suggesting more functional organization of hPECs. We established a bioengineering 3D culture system to promote robust and functional acinar-like organoids from hPECs. PCL nanofibrous microwells can be applied in the future for bioengineering of an artificial bio-salivary gland for restoration of salivary function. Statement of Significance: Three dimensional (3D) cultures of salivary glandular epithelial cells using nanofibrous bottom facilitate the formation of acinar-like organoids. In this study, we adapted a PEG hydrogel-micropatterned PCL nanofibrous microwell for the efficient bioengineering of human salivary gland organoids, in which we could easily produce uniform size of 3D organoids. This 3D culture system supports spherical organization, gene and protein expression of acinar markers, TJ proteins, adherence, and cytoskeletal proteins, as well as to promote epithelial structural integrity and acinar secretory functions, and results showed superior efficiency relative to Matrigel and nanofibrous scaffold culture. This 3D culture system has benefits in terms of inert, non-animal and serum-free culture conditions, as well as controllable spheroid size and scalable production of functional SG organoids and is applicable to bioengineering approaches for an artificial bio-gland, as well as to investigations of salivary gland physiology and regeneration.